Uncertainties and dispersion assessment: some challenges associated with missile aerodynamics. (1st March 2010) - Pagan, Didier; Taylor, Nigel; Hold, Roland; Toffi, Enrico
Missile aerodynamics addresses a speed range extending from low subsonic to high supersonic and the full range of vehicle incidence and body roll angles. Furthermore, airframe design is constrained by many operational aspects. This paper presents an overview of specific challenges associated with data uncertainty and dispersion assessment for missile aerodynamics and gives several examples for autopilot design, thrust-drag assessment in the different flight conditions and clearance from aircraft. Some of these challenges are at the leading edge of the present knowledge as the prediction of the thrust-drag balance of a hypersonic air-breathing vehicle of the accurate evaluation of the risk probability of a missile separation.